Transformações no uso da terra em áreas de preservação permanente: uma análise comparativa entre duas bacias hidrográficas com vocações econômicas distintas e as políticas ambientais vigentes - Vanzo, Gabriel (Universidade Federal de São Carlos, 2025)
In recent decades, land use in the state of São Paulo has undergone intense changes due to various economic cycles, often in violation of environmental regulations, especially with regard to Permanent Preservation Areas (APPs) and watersheds. This study aims to evaluate temporal changes in land cover and use in APPs located in the Tietê-Jacaré River (UGRHI-13) and Sorocaba/Médio Tietê River (UGRHI-10) watersheds from 2012 to 2023. The methods are based on the analysis of historical series from MapBiomas Collection 9, with spatial clippings obtained via QGIS version 3.34 and cross-referenced with the general boundaries of the APPs, whose delimitation must consider the parameters recommended by Federal Law No. 12,651/2012. Using geotechnologies, the areas of native vegetation, agricultural use, urban use, and other coverages in APPs were quantified, allowing for comparative analyses between the two basins and between the years 2012 and 2023. The results indicate contrasting patterns between the basins: while UGRHI-13 maintained a predominance of agriculture in the APPs, with low forest restoration over the period, UGRHI-10 showed a moderate increase in native vegetation despite the continuous advance of urbanization. The persistence of intensive anthropic use along watercourses suggests limitations in the implementation of forestry legislation and highlights the need for integrated policies that combine enforcement, economic incentives, and restoration actions. The analysis reinforces the relevance of automated classification systems, such as MapBiomas, for monitoring large-scale environmental changes, providing consistent data for territorial planning and water resource management. In summary, the units evaluated show different responses to land use pressures, highlighting that the effectiveness of APP conservation depends directly on regional socioeconomic dynamics and environmental governance capacity.
Changes in land use in permanent preservation areas: a comparative analysis between two watersheds with different economic vocations and current environmental policies
Keywords: Uso e cobertura da terra; Bacia hidrográfica; Legislação ambiental; Geotecnologias; Planejamento territorial; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::PLANEJAMENTO INTEGRADO DOS RECURSOS HIDRICOS; 6. Água Potável e Saneamento; 11. Cidades e Comunidades Sustentáveis; 3. Saúde e Bem-Estar